Effects of the sand content of muddy water content on one-dimensional vertical infiltration characteristics and dense layer formation characteristics - Kang, Shouxuan; Fei, Liangjun; Zhong, Yun; Liu, Lihua (International Journal of Agricultural and Biological Engineering, 2024)
Muddy water irrigation, an effective water-saving irrigation method, has been widely used in the Yellow River Basin in China. To investigate the effect of sand content on water infiltration and dense layer formation under one-dimensional vertical infiltration of muddy water, muddy water infiltration experiments were performed in the laboratory, and five sand contents of muddy water (S=0%, 3%, 6%, 9%, and 12%) were used. Models were established to describe the relationship between the cumulative infiltration amount [I(t)] and the infiltration duration (t); the relationship among the migration distance of the wetting front (Z), S, and t; the thickness of the sedimentary layer [H(t)]; and the relationship between S and t. The results revealed that I(t) and Z decreased significantly with the increase of sand contents, while H(t) increased significantly with the increase of sand contents. I(t) and Z were in the range of 7 cm and 20 cm for each treatment, respectively. The variation in I(t) with t fitted Kostiakov and Philip models, and the coefficients of determination were all greater than 0.99. With the increase in S, the infiltration coefficient gradually decreased, the infiltration index gradually increased, and the sorptivity gradually decreased. The particle composition of the sedimentary layer was similar to that of the argillaceous sediment, and the content of particles with a size of less than 2 mm in the sedimentary layer was lower than that of the argillaceous sediment. Compared with the original soil, the content of particles with a size of less than 0.05 mm and physical clay particles (diameter less than 0.01 mm) in the soil with an infiltration depth of 0-2 cm increased. The retention layer was from the topsoil to the infiltration depth of approximately 2 cm. This study can provide a scientific basis for further research on soil infiltration mechanisms under muddy water.Keywords: muddy water, sand content, dense layer, cumulative infiltration, wetting front transport, deposit layer thicknessDOI: 10.25165/j.ijabe.20241701.7919Citation: Kang S X, Fei L J, Zhong Y, Liu L H. Effects of the sand content of muddy water content on one-dimensional vertical infiltration characteristics and dense layer formation characteristics. Int J Agric & Biol Eng, 2024; 17(1): 172-179.